2020
DOI: 10.5038/1944-0472.13.1.1791
|View full text |Cite
|
Sign up to set email alerts
|

ISIS in Their Own Words: Recruitment History, Motivations for Joining, Travel, Experiences in ISIS, and Disillusionment over Time – Analysis of 220 In-depth Interviews of ISIS Returnees, Defectors and Prisoners

Abstract: Two hundred and twenty Islamic State of Iraq and Syria (ISIS) defectors, returnees, and imprisoned ISIS cadres were in-depth interviewed by the author, a research psychologist working for the International Center for the Study of Violent Extremism (ICSVE) from 2015-2019. These interviews were conducted in Turkey, Iraq, Syria, the Balkans, Europe, and Central Asia with ISIS prisoners, returnees, and defectors. The purpose was to learn about their recruitment history, motivations for joining, travel, experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 3 publications
0
15
0
4
Order By: Relevance
“…ISIS attracted many of its 40,000-45,000 FTFs through slick propaganda videos portraying a utopian vision of their Caliphate, governed purely by Allah's laws, but they also used Assad's atrocities as a foil to draw foreign terrorist fighters into the battleground in Syria. FTFs who left their home countries primarily between 2014 and 2016 were largely convinced that ISIS was going to deliver on its many promises and vision of Islamic living, but many were disappointed by the corruption, brutality and un-Islamic nature of what they witnessed and experienced and they also became disillusioned by ISIS failures to focus on the battle with Assad, even cooperating with his government (Speckhard & Ellenberg, 2020). Those FTFs who came before the establishment of the Caliphate, however, were not necessarily initially drawn by dreams of living a truly Islamic life or building an Islamic State in Syria and Iraq, but by a deep desire to help the Syrian people and to fight against Bashar al Assad, whom democratic leaders around the world also acknowledged was committing atrocious crimes against humanity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ISIS attracted many of its 40,000-45,000 FTFs through slick propaganda videos portraying a utopian vision of their Caliphate, governed purely by Allah's laws, but they also used Assad's atrocities as a foil to draw foreign terrorist fighters into the battleground in Syria. FTFs who left their home countries primarily between 2014 and 2016 were largely convinced that ISIS was going to deliver on its many promises and vision of Islamic living, but many were disappointed by the corruption, brutality and un-Islamic nature of what they witnessed and experienced and they also became disillusioned by ISIS failures to focus on the battle with Assad, even cooperating with his government (Speckhard & Ellenberg, 2020). Those FTFs who came before the establishment of the Caliphate, however, were not necessarily initially drawn by dreams of living a truly Islamic life or building an Islamic State in Syria and Iraq, but by a deep desire to help the Syrian people and to fight against Bashar al Assad, whom democratic leaders around the world also acknowledged was committing atrocious crimes against humanity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, some in the present sample were influenced by high-quality ISIS videos advertising an idealistic Islamic life, free of harassment or discrimination. Still others were reached out to by recruiters, friends, or family, promising them a sense of belonging and personal significance (Speckhard & Ellenberg, 2020). Now, many of these ISIS fighters are imprisoned either by the SDF, in Iraq, or by their home countries, and deservedly so.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some assumptions can be made based on the implications of these findings regarding gender perception on recruitment and mobilisation within terrorist activity. Due to terrorist groups use of online capabilities, the ability to recruit and mobilise individuals has increased through a greater ease in disseminating information to followers [14,91]. This has especially increased during the pandemic where more individuals have felt anxious, disempowered and alone and have found a sense of community and solace in like-minded groups where inciting violence either in a virtual or physical environment, has been more so attractive than possibly before the pandemic [92].…”
Section: Gender Findings and Interpretationsmentioning
confidence: 99%
“…This article examined ISIS's magazines through the prism of marketing and narrative advertising, and uncovered another propagandist technique used by the group. It demonstrated that the group relied not only on the polarization of opinions and sparking anger, 83 or offering a utopian idea of a righteous state, 84 or religious rewards, 85 or promising some material benefits and an exciting adventure; 86 it was also speaking to its followers' desires to be a certain type of people, to create a certain image of themselves -powerful, special, strong, etc. -and it successfully used marketing to satisfy this desire.…”
Section: Discussionmentioning
confidence: 99%